Veza između pristupa poljoprivrednim zajmovima i ekonomskog učinka industrije kasave u Nigeriji: dokazi sa malih farmi za preradu u državi Ojo: Agricultural Loan and Cassava Processing net farm income - Omodara, Olabisi Damilola; Adetunji, Esther Oluwaseun; Oluwasola, Oluwemimo (Journal of Agricultural Sciences (Belgrade), 2022)
Agricultural loan is an essential tool for transforming commercial agriculture into profitable venture. In view of this, this study investigated determinants of access to agricultural loan and profitability of small-scale cassava processing and tested whether access to agricultural loan affected net-farm income of cassava processors in Oyo State using budgetary analysis, Endogenous switching regression and inverse probability weighted regression adjustment (IPWRA) as a robustness check. A multistage random sampling technique was employed to gather information from 120 cassava processors. The results revealed that female processors dominated cassava processing and processors had mean age of 41 years. Only 23% of the respondents had agricultural loan access, which is primarily sourced from non-farm friendly informal sources. Budgetary result showed that processors earned average net farm income of N10,449.87 (US$29.03) in a production cycle. Endogenous switching Regression analysis revealed that married and educated cassava processors that are socially inclusive, have a large processing unit and earn meager off-farm income are more likely to access agricultural loan.   Further, marital status, education, number of working household members and processing experience in cassava processing affected the net-farm income of processors that had access to agricultural loan. Business risks, small enterprise size and high interest rate formed the major constraints to agricultural loans access. From the foregoing, a need for technical support system among cassava processors is inevitable. More so, credit initiatives for cassava processing should give preference to young smallholder processors to boost their loan access opportunities.